Hubungan antara Dukungan Keluargam Status Pekerjaan dan Paritas Ibu dengan Perilaku Pemberian ASI Eksklusif - Firrizqi Krisdila Fauzi (Jurnal Keperawatan Muhammadiyah, 2019)
ABSTRACTObjective : to analyze the relationship between family support, occupation, and parity with exclusive breastfeeding behaviorMethods: This article used analytical descriptive with crossectional study design. The technique of sampling was done by simple random sampling with 41 sample. Data was collected by interview using questionnaire to mother who com to Posyandu Melati in 2017. Data analysis using Chi Square Test with Confidence Interval (CI) 95%.Results : Most of the respondent (61%) didn't do exclusive breastfeeding behavior. The result showed that there are relationship between family support with p value 0,023 (p<0,05) and occupation has p value 0,042 (p<0,05) with the exclusif breast feeding behavior. Only paritu that has no relationship with exclusive breastfeeding behavior (p=0,278).Conclusion: It can be concluded that family support and occupation have significant relation with excusive breastfeeding behavior. Meanwhile. parity does not have relation with exclusif breast feeding